MODEL PERILAKU INVESTOR KOTA MEDAN BERDASARKAN STRATEGI PEMASARAN - Arlina Nurbaity Lubis; Isfenti Sadalia; Khaira Amalia Fachrudin (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
Behavioral finance is very important in one's decision-making when investing. Many factors affect the financial investors in the process of financial investment decision. This study aims to: (1) for test whether there is any difference in the financial investment decision process when viewed from demographic variables such as occupation, gender, and age of financial knowledge, (2) for test the influence of internal factors consisting of perception, motivation, learning, financial knowledge and external factors consisting of product, price, place/location, promotion, physical evidence, process, people and customer service to the investor's decision. The type of this research is descriptive quantitative. The sample in this study consist of 100 financial investors in the city of Medan. Discriminant and multiple regression analysis with stepwise method is used to test the hypothesis. The results showed: (1) there are significantly differences in the process of financial investment decisions based on demographic variables such as occupation, gender, and financial knowledge. While there was no difference in the financial investment decision process based on age categories, (2) process, motivation and customer service variable, have a positive and significant impact on investors' decision.